Economic Empowerment Model Through the Umkm Corner Program Of Bank NTB Syariah in Mataram City - Lalu Suparman Ambakti; Yanti Budiasih (UIN Mataram, 2026)
This study analyzes the economic empowerment model through the UMKM Corner program of Bank NTB Syariah in Mataram City. This program represents an innovation by Islamic financial institutions to expand access to financing, business assistance, and financial literacy for UMKM actors. Using a descriptive qualitative approach, data were collected through interviews, observation, and documentation, then analyzed reductively. The results show that UMKM Corner contributes to improving managerial capacity, strengthening digital marketing networks, and expanding access to Islamic financing. This program not only drives local economic growth but also instills the values of justice, partnership, and sustainability in accordance with sharia principles.